2015
DOI: 10.1002/chem.201406346
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent Flavins: Rational Molecular Design for Quenching Protection Based on Repulsive and Attractive Control of Molecular Alignment

Abstract: Unprecedented intense fluorescent emission was observed for a variety of flavin compounds bearing a perpendicular cyclic imide moiety at the C7 position of an isoalloxazine platform. A series of alloxan-substituted flavins was prepared selectively by reduction of the corresponding N-aryl-2-nitro-5-alkoxyanilines with zinc dust and subsequent reaction with alloxan monohydrate in the presence of boric acid. Analogues bearing oxazolidine-2,4-dione functionality were obtained on methylation of the alloxan-substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Mechanistic investigations revealed that the present intense solid‐state emission arises from a structure‐specific preference for the planar conformation and multiplicity in hydrogen bonding fixation of the molecular unit to achieve enhanced energy transition probability and heat‐resistance properties in the crystalline state. This work clearly demonstrates the importance of repulsive and attractive control for restriction of molecular rotation to achieve intense solid‐state emission. Research is currently underway to apply this principle to the development of new light‐emitting functional materials.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Mechanistic investigations revealed that the present intense solid‐state emission arises from a structure‐specific preference for the planar conformation and multiplicity in hydrogen bonding fixation of the molecular unit to achieve enhanced energy transition probability and heat‐resistance properties in the crystalline state. This work clearly demonstrates the importance of repulsive and attractive control for restriction of molecular rotation to achieve intense solid‐state emission. Research is currently underway to apply this principle to the development of new light‐emitting functional materials.…”
Section: Discussionmentioning
confidence: 72%
“…As part of a program to create highly fluorescent and phosphorescent materials based on the three‐dimensional synthetic alteration of less‐ or proemissive platforms, we investigated the emission properties of a series of zwitterionic imidazolium N ‐arenolates (Scheme ),, and found that 2‐pyridin‐3‐olate isomer 1 exhibits intense solid‐state fluorescence exclusively in the crystalline state at ambient temperature. All the other zwitterionic analogues with various functionalities are non‐ or less emissive under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from those specially designed FL-based fluorescent sensors, 35–39 substitution on the benzene ring was shown to efficiently modulate the photophysical properties and many artificial FLs, 41 including isopropyl-, 42 bromo-, 27,31,43 iodo-, 19 trifluoromethyl-, 43 amino-, 41,44–48 fluoro- 40,49,50 and methyl-modified 51,52 FLs were designed as fluorescent sensors or photosensitizers. 18–53 AmFLs are an important group within the large family of FLs and a number of AmFLs, such as roseoflavin, etc. , exist in organisms and possess antibacterial, anticancer and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of the literature indicated that this oversight is due to a lack of a general procedure for installing an aryl group in the benzene ring of flavins. With one nongeneral exception, the synthesis of C7- and C8-arylated flavins has been accomplished by means of the sequential cyclization of aniline derivatives (Scheme a) . It should be noted that the step-by-step construction of a flavin moiety is not effective because it requires a specific approach for each derivative and is characterized by a limited scope.…”
Section: Introductionmentioning
confidence: 99%